AKTIVITAS PETANI GAMBIR TRADISIONAL DI KECAMATAN KAPUR IX DALAM KARYA SENI GRAFIS - NAHDATUL AZMI, Yofita Sandra, S.Pd., M.Pd., Drs. Syafei, M. Ag. (Universitas Negeri Padang, 2017)
The purpose of this final paper is to visualize the activities of traditional gambir farmers in Kapur IX District in the work of Graphic Arts with Relief Print technique, namely Hardboard Cut. Gambir farmer activity starts from gambier leaf making, leaf processing until the sap comes out, freezing sap, gambier painting, and drying. Activities they do aim to meet their basic needs such as clothing, food, and boards. The method of creation of this final paper uses 5 stages of preparation, elaboration, synthesis, concept realization, and completion, and the last one to hold painting exhibition by using oil paint media on paper.